Ekologi Spiritual dalam Novel Glonggong Karya Junaedi Setiyono dan Jatisaba Karya Ramayda Akmal (Jurusan Tadris Bahasa Indonesia, 2019)
This study aims to describe 1) the ecological dimension of Javanese in the Glonggong by Junaedi Setiyono and the Jatisaba by Ramayda Akmal; 2) the influence of Javanese spirituality in environmental management in the Glonggong and Jatisaba. The technique used in data collection was reading techniques and note-taking techniques. The data analysis technique used was descriptive qualitative. Validity used semantic validity technique. The results of the study, there are two forms of interrelationships between environment and humans, namely 1) humans are subject to nature, and 2) humans master nature. From the two forms of relationship, there is a Javanese spirituality that influences environmental management, including saduluran (kinship), bisa ajer ajur (able to adapt and select), and nrimo ing pandhum (accept all gifts or sincerity).Â Penelitian ini bertujuan mendeskripsikan dimensi ekologi orang Jawa dalam novel Glonggong karya Junaedi Setiyono dan Jatisaba karya Ramayda Akmal serta pengaruh spiritualitas orang Jawa dalam pengelolaan lingkungan pada novel Glonggong dan Jatisaba. Teknik pengumpulan data dalam penelitian ini adalah teknik baca dan catat. Teknik analisis data yang digunakan berupa deskriptif kualitatif. Validasi data menggunakan validitas semantik. Hasil penelitian menunjukkan dua bentuk hubungan lingkungan dengan manusia, yaitu 1) manusia tunduk pada alam, dan 2) manusia menguasai alam. Dari kedua bentuk hubungan tersebut terdapat spiritualitas Jawa yang memengaruhi pengelolaan lingkungan, antara lain saduluran (kekerabatan), bisa ajur ajer (mampu beradaptasi dan menyeleksi), dan nrima ing pandhum (menerima segala pemberian atau ikhlas).